Buckling Analysis of Belly Shaped Composite Column - Kesavan, S; Ramesh, S; ., Alexabhishek; S.Sudarsan, J; Vanamoorthy kumaran, P; Muthukumar, G (International Journal of Engineering and Technology, 2018)
The study of Non prismatic column is designed to minimize the volume of material in the column by changing its shape, the column is subject to both buckling and strength constraints under axial compression load. The belly column is designed as Encased Composite column to improve the strength and ductility of column. The effective use of material through optimal shape of the column. Five models have been created in ANSYS WORKBENCH and all the columns having the same volume of materials, fixed end conditions and length of column. The behaviour of non-prismatic column is always based on tapering ratio and the slenderness ratio of the column. As the taper ratio increases, the elastic buckling load increases and stress decreases in the mean while the maximum stress occurs in the prismatic column compared with the non-prismatic column. As a result of this analysis Equivalent stress, Equivalent elastic strain, Total Deformation and Buckling load Deformation was observed and hence Stress-Strain graphs, Load -Deformation graphs and Mode-Load multiplier graph had been plotted.Â Â